Three-Dimensional Cell Culture Models to Investigate Oral Carcinogenesis: A Scoping Review - Chitturi Suryaprakash, Ravi Teja (Int J Mol Sci, 2020)
Three-dimensional (3-D) cell culture models, such as spheroids, organoids, and organotypic cultures, are more physiologically representative of the human tumor microenvironment (TME) than traditional two-dimensional (2-D) cell culture models. They have been used as in vitro models to investigate various aspects of oral cancer but, to date, have not be widely used in investigations of the process of oral carcinogenesis. The aim of this scoping review was to evaluate the use of 3-D cell cultures in oral squamous cell carcinoma (OSCC) research, with a particular emphasis on oral carcinogenesis studies. Databases (PubMed, Scopus, and Web of Science) were systematically searched to identify research applying 3-D cell culture techniques to cells from normal, dysplastic, and malignant oral mucosae. A total of 119 studies were included for qualitative analysis including 53 studies utilizing spheroids, 62 utilizing organotypic cultures, and 4 using organoids. We found that 3-D oral carcinogenesis studies had been limited to just two organotypic culture models and that to date, spheroids and organoids had not been utilized for this purpose. Spheroid culture was most frequently used as a tumorosphere forming assay and the organoids cultured from human OSCCs most often used in drug sensitivity testing. These results indicate that there are significant opportunities to utilize 3-D cell culture to explore the development of oral cancer, particularly as the physiological relevance of these models continues to improve.